FROM FLIPPED CLASSROOMS TO GAMIFICATION: A DEEP DIVE INTO CONTEMPORARY ENGLISH TEACHING METHODS: NURFITRI - NURFITRI, NURFITRI (JURNAL ADMINISTRASI NUSANTARA, 2024)
This article explores the implementation of contemporary teaching methods, specifically flipped classrooms and gamification, in English language instruction. Delving into the challenges and opportunities faced by educators, the study investigates the impact on student engagement, comprehension, and overall language proficiency. The discussion navigates technological disparities, curriculum integration, student accountability, and the transformative potential of personalized learning, increased engagement, immediate feedback, and active learning. As educators strive to overcome challenges and leverage opportunities, the article contributes to the ongoing evolution of language education, shaping a future where students not only master language proficiency but also cultivate a love for continuous learning.